Identification of a variant in NLRP3 gene in a patient with Muckle-Wells syndrome: a case report and review of literature - Jia Liu; Ranran Zhang; Zhi Yi; Yi Lin; Hong Chang; Qiuye Zhang (BMC, 2023)
Abstract Background Cryopyrin-associated periodic syndrome (CAPS), a rare genetic autoimmune disease, is composed of familial cold autoinflammatory syndrome (FCAs), Muckle-Wells syndrome (MWS), and neonatal onset multisystem inflammatory disease (NOMID). MWS is caused by dominantly inherited or de novo gain-of-function mutations in the NOD-like receptor 3 (NLRP3) gene. At present, there is no report about the variation of R262W in China. Case presentation We reported a 3-year-old Chinese boy who had recurrent fever without obvious inducement, bilateral conjunctival congestion, and urticarial-like rash. Laboratory examination showed elevation in leukocyte count, neutrophil count, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) and serum amyloid protein (SAA) levels. Whole exome sequencing identified a missense variation c.784-786delinsTGG (p.R262W) in the coding region of the NLRP3 gene. Conclusion A classical variant of the NLRP3 gene in a patient with MWS was first reported in China.